With great power, comes great responsibility: the importance of broadly measuring Fc-mediated effector function early in the antibody development process - Silvia Crescioli; Shashi Jatiani; Lenny Moise (mAbs)
The field of antibody therapeutics is rapidly growing, with over 210 antibodies currently approved or in regulatory review and ~ 1,250 antibodies in clinical development. Antibodies are highly versatile molecules that, with strategic design of their antigen-binding domain (Fab) and the domain responsible for mediating effector functions (Fc), can be used in a wide range of therapeutic indications. Building on many years of progress, the biopharmaceutical industry is now advancing innovative research and development by exploring new targets and new formats and using antibody engineering to fine-tune functions tailored to specific disease requirements. In addition to considering the target and the disease context, however, the unique features of each therapeutic antibody trigger a diverse set of Fc-mediated effector functions. To avoid unexpected results on safety and efficacy outcomes during the later stages of the development process, it is crucial to measure the impact of antibody design on Fc-mediated effector function early in the antibody development process. Given the breadth of effector functions antibodies can deploy and the close interplay between the antibody Fab and Fc functional domains, it is important to conduct a comprehensive evaluation of Fc-mediated functions using an array of antigen-specific biophysical and cell-mediated functional assays. Here, we review antibody and Fc receptor properties that influence Fc effector functions and discuss their implications on development of safe and efficacious antibody therapeutics.